Evaluation of samplers and filter materials for the establishment of trace metal concentration profiles in peat bog porewaters using inductively coupled plasma-mass spectrometry - Rausch, Nicole; Ukonmaanaho, Liisa; Nieminen, Tiina M.; Krachler, Michael; Le Roux, Gaël; Shotyk, William (Analytica chimica acta, 2006)
Two different types of sampler were used for the collection of humic-rich porewaters from ombrotrophic bogs at background and contaminated sites: a syringe-type sampler, which required manual filtration and dialysis chambers (peepers) where samples were filtered in situ. Concentrations of 10 trace elements Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb, V and Zn have been determined in the collected porewater samples using inductively coupled plasma-sector-field-mass spectrometry. The accuracy of the analytical procedures was evaluated by the regular analyses of the two certified riverine water reference materials SLRS-2 and SLRS-4, respectively. For the syringe-type sampler, four different 0.45μm syringe filters were tested. Low blank values together with sufficiently low filtration artefacts were obtained using unwashed GD/XP filters (Whatman). When pre-cleaned filters were used, Cu and Mo showed strong filtration artefacts. Mean metal concentrations of filtrates differed by up to five times, depending on the filter type used. Overall blank values of the sampling devices were as follows (ngl−1): Cd 1, Co 9, Cr 50, Cu 70, Mn 200, Mo 20, Ni 100, Pb 4, V 10, Zn 1000. The contribution of atmospheric dust during the on-site filtration might have enhanced overall blank levels of Cr, Cu and Zn when protective covers were not used during sample collection/on-site filtration. Metal concentrations at background sites were at ngl−1 levels except for Zn and Mn (low μgl−1). With the exception of Co and Mn, dialysis chambers were not suitable for sampling porewaters at these concentration levels.
Available online 20 December 2005
Gesehen am 29.09.2020